Liolaemus olongasta (Chelco Lizard): Endoparasites - Castillo, Gabriel Natalio (2019)
A total of 158 species of the genus Liolaemus occur in Argentina (Abdala and Quinteros 2014. Cuad. Herpetol. 28:55–82). In Argentina, L. olongasta is distributed in San Juan, Mendoza, and Rioja provinces (Abdala et al. 2012. Cuad. Herpetol. 26:215–248). It is mainly insectivorous and has a unimodal activity pattern (Acosta et al. 2017. Los Reptiles de San Juan. Editorial Brujas, Córdoba. 130 pp.). It is currently categorized as a non-threatened species (Abdala et al. 2012. Cuad. Herpetol. 26:215–248). Here, we report on the helminth endoparasites in the gastrointestinal tracts of L. olongasta in Matagusanos, San Juan Province, Argentina. In February 2017, three specimens of L. olongasta (adult males: mean SVL = 5.9 ± 0.17 cm, range: 5.7–6 mm; weight = 7.4 ± 0.37 g, range (7–7.7 g) were collected at Matagusanos, San Juan Province (31.24638°S, 68.62916°W; 910 m elev.). Phytogeographically, the area is included in the Monte. The stomach and intestines were longitudinally slit, and their contents were examined using a microscope. The dissection revealed one type of prey item and nematodes. The nematodes found were stored in 70% ethanol. Nematode observation and identification was done using the diaphanization by lactophenol technique. The specimens were deposited in the parasitological collection of the Department of Biology, National University of San Juan (UNSJPar254). A dissection of the animal revealed recent ingesta that included one scorpion. A total of two nematodes larvae of the genus Physaloptera were isolated from the stomachs of one adult specimen (infection prevalence = 33.3%, with a mean intensity of 2 and mean abundance of 0.66). Species of the genus Physaloptera occur in the stomach of a variety of terrestrial vertebrates (Goldberg and Bursey 1989. J. Wildl. Dis. 25:425–429). Larvae are common in amphibians and lizards (Anderson 2000. Nematode Parasites of Vertebrates: Their Development and Transmission. CABI Publishing, Oxon, U.K. 650 pp.). Currently, there are 100 Physaloptera described, including valid and inquirendae species, nine of these were described from reptiles (Pereira et al. 2012. J. Parasitol. 98: 1227–1235). In Argentina, Physaloptera has been reported the following reptiles: Liolaemus quilmes, Liolaemus ornatus, Liolaemus alticolor (Ramallo and Díaz 1998. Bol. Chil. Parasitol. 53:19–22), Tropidurus etheridgei (Cruz et al. 1998. Herpetol. Nat. Hist. 6:23–21), Leiosaurus catamarcensis, Leiosaurus belli, Liolaemus neuquensis (Goldberg et al. 2004. Comp. Parasitol. 71:208–214), Liolaemus koslowskyi, Liolaemus darwinii (O’Grady and Dearing 2006. Oecologia 150:355– 361), and Xenodon merremi (Lamas et al. 2016. Facena 32:59–67). Physaloptera sp. in Liolaemus olongasta is a new host record from Argentina.